Toward an Understanding of the Poor Health Status of Indigenous Australian Men. (December 2016) - Mellor, David; McCabe, Marita; Ricciardelli, Lina; Mussap, Alex; Tyler, Matthew
The purpose of this study was to investigate perceptions of health and health behaviors among Indigenous Australian men. Using a participatory action research (PAR) framework, we conducted two focus groups and 40 individual semi-structured interviews with men between the ages of 18 and 35 years in each of three locations across Australia. We used the health beliefs model to provide a framework for the analyses. Participants recognized that their Indigenous status placed them in a vulnerable position with regard to health, and that there might be serious consequences of failing to follow a good diet and engage in appropriate exercise. However, they delineated a number of barriers to engaging in such health behaviors. These perceived barriers require addressing at a range of policy levels within government, with a focus on social structures and institutionalized discrimination, as well as unemployment, poverty, dispossession, and cultural oppression.